2018
DOI: 10.3390/pharmaceutics10020069
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid Chromatography-Quadrupole-Time-of-Flight Mass Spectrometric Assay for the Quantification of Fabry Disease Biomarker Globotriaosylceramide (GB3) in Fabry Model Mouse

Abstract: Fabry disease is a rare lysosomal storage disorder resulting from the lack of α-Gal A gene activity. Globotriaosylceramide (GB3, ceramide trihexoside) is a novel endogenous biomarker which predicts the incidence of Fabry disease. At the early stage efficacy/biomarker study, a rapid method to determine this biomarker in plasma and in all relevant tissues related to this disease simultaneously is required. However, the limited sample volume, as well as the various levels of GB3 in different matrices makes the GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This may be a result of limited biodistribution of the enzyme to the kidney, but it may also relate to the hydroxylated Gb3 species that are expressed in the kidney and seemingly impervious to ERT. Several studies have explored Gb3 glycolipid profiles in Fabry disease mouse models and the effects of ERTs on these, but the coverage of Gb3 glycolipid species were inconsistent and often not comprehensive (Togawa et al, 2010;Durant et al, 2011;Shin et al, 2018). The most comprehensive study of Gb3 profiles performed on organs from Fabry disease mice found that the di-hydroxylated Gb3 isoforms are quite prevalent in kidney (Ishii et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of limited biodistribution of the enzyme to the kidney, but it may also relate to the hydroxylated Gb3 species that are expressed in the kidney and seemingly impervious to ERT. Several studies have explored Gb3 glycolipid profiles in Fabry disease mouse models and the effects of ERTs on these, but the coverage of Gb3 glycolipid species were inconsistent and often not comprehensive (Togawa et al, 2010;Durant et al, 2011;Shin et al, 2018). The most comprehensive study of Gb3 profiles performed on organs from Fabry disease mice found that the di-hydroxylated Gb3 isoforms are quite prevalent in kidney (Ishii et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Gb3 was determined by LC‐MS/MS according to a published procedure with modifications 27 …”
Section: Methodsmentioning
confidence: 99%
“…The presence of Gb3 analogs containing lyso-Gb3 analogs has been suggested in Gla knockout mouse organs (28,29) and the plasma of patients with Fabry disease (19), but this is the first experimental data demonstrating the presence of Gb3 analogs in mouse organs. LC-MS/MS has been widely used to determine Gb3 content in the plasma of patients with Fabry disease (13) and in mouse organs (31,32), and it can detect selected Gb3 isoforms but not Gb3 analogs. In this study, Gb3 analogs constituted <2% of the standard Gb3 from Matreya LLC; however, significant amounts of Gb3 analogs were observed in the heart, kidneys, and liver (approximately 12, 30, and 16%, respectively) of our mouse model (Table 1).…”
Section: Deacylation Of Gb3 From Different Organs Of Gla Tm Tg(cag-a4mentioning
confidence: 99%